Inclusive Education Management Strategies in the Digital Era: Addressing Challenges and Seizing Opportunities for Equitable Access to SDG 4 - Sofia Annisa Rahma; Anindya Larasati Ramadhani; Rona Angelica Zahra (Managere: Indonesian Journal of Educational Management, 2025)
This study examines education management strategies crucial for achieving inclusive education and equitable access in the digital era, in alignment with Sustainable Development Goal 4. The primary issue raised is the disparity in access to and quality of education that still exists, particularly for vulnerable groups, amid rapid digital transformation. The study employs a qualitative design with a case study approach, utilizing in-depth interviews and document analysis as data collection methods, along with thematic analysis for data interpretation. The study's findings revealed that learning strategies and personalized instruction are crucial for accommodating the diversity of students, supported by the adaptation of teaching methods, the use of technology, and active collaboration among teachers, school management, and parents. However, the implementation of inclusive education in the digital age faces significant challenges, including limited access to technology infrastructure, a lack of teacher training in the use of inclusive technology, and a widening digital divide. On the other hand, digital technology also presents a significant opportunity to create a more adaptive, engaging, and equitable learning environment, which can ultimately enhance student motivation and participation. This research contributes to the literature by providing an in-depth and holistic qualitative analysis of the synergy between learning personalization, digital challenges, and technological opportunities in the context of inclusive education. The study's implications include specific recommendations for policy development that support the equitable distribution of digital infrastructure and teacher training, as well as practices that encourage multi-stakeholder collaboration.